Effects of a CrossFit Training Program on Body Composition and Hematological Parameters in Young Soccer Players - Alsharab, Omar; Triki, Raoua; Jebabli, Nidhal; Khalfoun, Jihen; Zouhal, Hassane; Ben Abderrahman, Abderraouf (Advances in Social Sciences Research Journal, 2024)
The study aimed to identify the effects of CrossFit training on body composition and hematological parameters in young soccer players. Forty soccer players voluntarily took part in this study, they were divided randomly into two equal groups: Experimental group (N=20) underwent a 12 weeks of CrossFit training program, and the control group (N=20) underwent 12 weeks of traditional training. Body composition and hematological parameters were measured before and after the experiment among both groups. As results, a significant time x group interaction effect was observed for body mass index (p=0.99; ES=0.45), body fat percentage (p=0.19; ES=0.36), and muscle mass (p=0.16; ES=0.57), which indicate a positively significant change of body mass index and body fat percentage, muscle mass (p<0.05). While a significant group x time effect was reported for body fat mass (p=0.04, ES=0.43) and basal metabolic rate (p=0.005, ES=0.55), with favor for experimental group compared to control group. Additionally results showed a statistically significant group x time effect for Hemoglobin (p=0.001; ES=0.24) Red blood cells (p=0.04, ES=0.56) and Hematocrit (p=0.007; ES=0.36) with favor for EG in comparison with CG group, an increasing was presents for all previous parameters respectively among experimental group (p<0.001). However, no statistically significant effect of group x time was indicated for platelets (p=0.16; ES=0.58), significant increasing was reported for both groups. CrossFit exercise program can be recommended as an effective program in enhancing and adjusting the vital indicators of young soccer players and improve performance.